Sismicidad inducida por el Terremoto de Limón - Barquero, Rafael (2011)
After the Limón Earthquake1 of April 22, 199|, seismic activity generated in several zones of the country such as: Matina, Moravia de Chirripó, Tucurrique, Orosi, Empalme, San Ignacio de Acosta, Irazú volcano and San Isidro de Pérez Zeledón. This activity, by its temporal and spatial relation to the Limón earthquake can be considered as “induced”. From the seismological analysis and tectonic characteristics of the different seismic zones studied two main groups were determined: a first group comprehends the Caribbean region of the country with a tectonic pattern of reverse type with strike slip component oriented and a second group characterized by normal type faults with strike slip component and predominant NE-SW and NW-SE orientations surrounding the Central Valley tectonic basin.